PENDAPATAN DAERAH, BELANJA DAERAH DAN PERTUMBUHAN EKONOMI DI KOTA/KABUPATEN KALIMANTAN BARAT - Magdalena Nany; Mujiyono Mujiyono; Seseliya Seseliya (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2022)
The objective of this research was to give empirical evidence about the effects of Original Local Government Revenue, Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds, and Regional Expenditure on economic growth. One hundred and forty three data from 13 districts and municipalities in West Kalimantan province during 2008-2018 were analyzed by multiple regression analysis. The results show that Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds and Regional Expenditure have significant effects on economic growth. However Original Local Government Revenue do not have significant effects on economic growth.